Implementasi Manajemen Anak Didik Berkebutuhan Khusus di TK Inklusi Islam Pelangi Anak Negeri Yogyakarta - Hasanah, Raudatul (ACIECE, 2019)
The management of students with special needs is one of the efforts to manage or organize the school so that the needs of students with special needs are more managed and organized. This study aims to find out how the implementation of the management of students with special needs in the Islamic Inclusion Pelangi Anak Negeri Yogyakarta. This research is a field research using a descriptive qualitative approach. The subjects in this study were principals and teachers in Pelangi Anak Inclusive Islam State Kindergarten and the object in this study was the management of students with special needs that were applied in Pelangi Anak Inclusion Islam Kindergarten. Data and information in this study were obtained by interview, observation and documentation. The results of this study are: The implementation of the management of students with special needs in the Islamic Inclusion Pelangi Anak Negeri has been going well, but there are some things that need to be improved. The management of students with special needs in TK Pellusi Islam Pelangi Negeri is implemented according to the stages, including: (1) Acceptance of students by analyzing needs, student recruitment and coaching, (2) Recording of learning achievements, (3) Recording guidance and counseling students, and (4) Monitoring